PENERAPAN METODE SUKU KATA (SILABEL) DALAM PEMBELAJARAN MEMBACA PERMULAAN BAHASA INDONESIA SISWA KELAS II DI UPT SDN 20 TURATEA KAB. JENEPONTO - Andi Zulqaedah Jafar; M. Agus; Abdul Rajab (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the application of the syllable method in teaching Indonesian language beginning reading for second-grade students at the UPT SDN 20 Turatea, Jeneponto Regency. This study uses a qualitative approach with a descriptive research type. Data collection techniques include observation, interviews, student work, and documentation. The collected data were then analyzed through data reduction, data presentation, and conclusion drawing. The subjects in this study were second-grade teachers and 20 second-grade students at the UPT SDN 20 Turatea, Jeneponto Regency. The results show that the application of the syllable method in teaching reading has been implemented well and in accordance with the steps of the syllable method, which introduces letters, then arranges them into syllables, then continues into words, and finally simple sentences. The study shows that student abilities vary; of the 20 students, 40% are able to read fluently, 40% are able to read although still stuttered, and 20% are still at the spelling stage. This shows that 80% of students have acquired reading skills and have experienced development in their initial reading skills through the application of the syllable method, although with varying levels of fluency. Based on the results of the study above, it can be concluded that the application of the syllable method in the initial reading learning of Grade II students at UPT SDN 20 Turatea, Jeneponto Regency has been proven to have been implemented well and can develop students' reading skills gradually.